Revealing Moments of Mentorship: Social Exchanges Between a Graduate Research Assistant and a Professor - Saudelli, Mary Gene; Niemczyk, Ewelina Kinga (Alberta Journal of Educational Research, 2020)
This is a longitudinal self-study of a mentoring relationship that emerged and evolved between a graduate research assistant and a professor over seven academic years. We use social exchange theory to explore the evolution of this relationship. Specifically, our focus is a series of nine revealing moments that demonstrate evident learning, a relationship change, or shifts in the currencies of exchange over time. These revealing moments arose from intentional opportunities for scholarly development, personal and relational interactions, and unanticipated occurrences. This study exemplifies the dynamics of a mentoring relationship over an extended time period, thereby responding to the dearth of longitudinal studies of mentoring internationally. Key words: mentoring; social exchange theory; mentoring relationships; graduate education; research assistantships Ce projet de recherche est une étude longitudinale de soi portant sur une relation de mentorat qui a évolué entre un assistant de recherche de cycle supérieur et un professeur au cours de sept années académiques. Nous nous appuyons sur la théorie de l’échange sociale pour explorer cette relation. Plus précisément, nous nous penchons sur neuf moments révélateurs qui démontrent soit un apprentissage évident, un changement dans la relation ou l’évolution des échanges. Ces moments révélateurs ont découlé d’occasions délibérées visant le développement de la recherche; des interactions personnelles et relationnelles; et des événements inattendus. Cette étude illustre la dynamique d’une relation de mentorat au fil du temps, apportant ainsi une réponse au manque, à l’échelle internationale, d’études longitudinales portant sur le mentorat. Mots clés: mentorat, théorie de l’échange sociale, relation de mentorat, études supérieures, assistanat à la recherche